An Empirical Study to Assess the Impact of Greenwashing on Customer Purchase Decisions: A Case Study of the Grocery Retail Sector in the United Kingdom - Abbaszada, Nariman (Digital Repository of Theses, 2026)
Greenwashing has emerged as a matter of concern in the UK grocer retail sector as retailers turn to sustainability discourse to influence the purchase of their products by eco-friendly customers. Nonetheless, exaggerated or misleading environmental reporting is deceptive to consumer knowledge and affects the buying behavior. Even though regulatory focus and consumer awareness is on the increase, greenwashing practices are here to stay because there is a high level of information asymmetry between the retailers and the consumers. This paper examines how greenwashing influences customer buying behaviour in the UK grocery market along four major dimensions of sustainability communication namely transparency, accountability, content of sustainability reports, and the adherence to quantifiable environmental criteria. The study is based on the Theory of Planned Behavior, AIDA, Elaboration Likelihood Model, Signaling Theory and Information Asymmetry Theory, and has been formulated to explain the way in which consumers process sustainability claims and make purchase intentions. Despite emphasizing the need to maintain transparency, credible reporting, and third-party certification in instilling consumer confidence, the empirical research in the UK grocery retail situation, especially regarding the significance of measured standards, has been low. The research adheres to a deductive and quantitative approach since it adopts a positivist philosophy. It used a cross-sectional survey design to collect primary data with the help of a structured questionnaire that was distributed to consumers of the UK grocery. The SPSS was used to analyse data with the help of descriptive statistics, correlation analysis, and multiple regression. The independent variables were taken to be transparency, accountability, sustainability report content and measured standards, whereas the dependent variable was customer purchase decision. Cronbach alpha and construct validity tests were used to guarantee reliability and validity. The results indicate that there is an intention-credibility gap and consumers have expressed more sustainable purchase intentions than the confidence in sustainability claims of retailers. Correlation analysis revealed that there were moderate positive relations between all independent variables and purchase decisions (r = 0.499- 0.574). The regression model accounted 68.5 percent of the variation in the decisions of customers to buy a product with transparency becoming the best predictor (b = 0.397, p <.001). The paper concludes that to decrease greenwashing, increase consumer trust, and empower people to make informed and responsible purchasing decisions in UK grocery retail sector, the sector needs more accurate and transparent reporting on sustainability, measurable standards, accountability, and credible reporting on sustainability. KEYWORDS: Grocery Retail Sector, Transparency, Customer Purchase Decision, Accountability, Contents, Standards